Hole sealing agent for coal mine
By adding composite additives and inhibiting microspheres to the coal mine sealing agent, the problem of good permeability of the sealing agent is solved, and better sealing effect and safety are achieved.
Patent Information
- Application Number
- CN202411841145.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
Existing coal mine sealing agents are prone to flow when they have good permeability, resulting in poor sealing effect and may cause gaps and safety hazards.
By adding composite additives and inhibiting microspheres to the sealing agent, the wetting and fluidity of the sealing agent are improved by adding composite additives to the sealing agent, inhibiting microspheres by water release inhibiting particles, and oxidizing sodium sulfamate to reduce fluidity.
Effectively promote the penetration of sealing agent deep into coal rock cracks, reduce the gaps formed by flow, improve the sealing effect and safety, and reduce rework and maintenance costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal seam drilling plugging, in particular to a sealing agent used in coal mines. Background Art
[0002] Coal mine drilling is an important part of coal mining operations, and after the borehole is excavated, it needs to be sealed before the next step. Sealing work is not only related to the safe production of the mine, but also to the life safety of the staff. Therefore, the sealing effect is very important for coal mine drilling work. The main sealing methods currently used are cement mortar sealing method, wooden wedge yellow mud sealing method, polyurethane foam sealing method and synthetic resin and cement slurry pressure grouting method. The coal seam is mainly composed of sandstone, with developed fracture zones and a large number of fractures. If the sealing liquid cannot fully penetrate into the coal seam fractures, it will lead to poor sealing effect. Therefore, the sealing agent needs to have good fluidity to improve the sealing effect. The cement mortar sealing method is to inject cement mortar into the borehole. The cement is closely combined with the borehole, and the cement mortar has good fluidity. It can penetrate into the coal rock mass cracks around the borehole. After the cement mortar solidifies and hardens, it can effectively seal the micro-cracks around the borehole. However, cement sealers have good fluidity and are prone to flow before they are completely solidified, forming gaps, affecting the sealing of the seals and resulting in poor sealing effects. Insufficient sealing may leave water seepage channels, affecting the grouting effect, and in the long run may cause safety accidents such as landslides. Therefore, insufficient sealing requires re-filling, which increases the workload and sealing costs.
[0003] Therefore, the present invention provides a sealing agent for coal mines, which promotes the sealing agent to penetrate into the sandstone cracks around the drill hole and prevents the sealing agent from flowing and causing gaps in the sealed hole. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a sealing device for coal mines, which solves the problem that cracks are easily formed in the sealing device due to the good permeability of the sealing agent.
[0005] The present invention solves the above technical problems by the following technical means:
[0006] A sealing agent for coal mines, the raw materials of the sealing agent are as follows: cement, bentonite, fly ash, epoxy resin, composite additives, inhibition microspheres, water, and the mass ratio thereof is (45-50): (5-8): (2-3): (8-10): (5-8): (4-6): (100-150).
[0007] Furthermore, the raw materials of the composite additive are as follows: sodium oleate, sodium aminosulfonate, and water, and the mass ratio thereof is (1-1.5): (1.6-2): (80-120).
[0008] Further, the preparation method of the composite additive is as follows:
[0009] Sodium oleate is added into water at 70-80° C., and stirred evenly to obtain a sodium oleate solution. After the solution is cooled to room temperature, sodium aminosulfonate is added thereto, and stirred evenly to obtain a composite additive.
[0010] Further, the preparation method of the inhibitory microspheres is as follows:
[0011] (1) adding sodium persulfate to water and mixing uniformly to obtain a sodium persulfate solution, then adding silica sol to the sodium persulfate solution and stirring uniformly to obtain a mixed solution;
[0012] (2) adding sodium carboxymethyl cellulose and N,N-methylenebisacrylamide to water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then adding the mixed solution, stirring evenly to obtain a mixed gel, drying the mixed gel at 30-40° C. for 4-6 hours, and then crushing to obtain inhibitory particles;
[0013] (3) adding glyceryl tristearate to anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0014] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0015] Furthermore, in the step (1) of preparing the inhibitory microspheres, the mass ratio of sodium persulfate, silica sol and water is (2-2.4): (3-4): (20-24).
[0016] Furthermore, in the step (2) of preparing the inhibitory microspheres, the mass ratio of sodium carboxymethyl cellulose, N,N-methylenebisacrylamide and water is (4-5):(0.2-0.25):(100-125), and the mass ratio of sodium carboxymethyl cellulose gel and the mixed solution is (4-5):(1-1.5).
[0017] Furthermore, in the step (3) of preparing the inhibitory microspheres, the mass ratio of glyceryl tristearate to gelatin is 1:1.
[0018] Furthermore, the particle size of the inhibition particles is 2-5 mm.
[0019] Furthermore, the particle size of the fly ash is 0.3-0.6 mm, and the particle size of the bentonite is 0.1-0.5 mm.
[0020] The main component of the sealing agent of the present invention is cement mortar, which has good fluidity, and is convenient for the sealing agent to penetrate into the borehole fissure. At the same time, a composite additive is added in the process of preparing the sealing agent. The sodium oleate in the composite additive can increase the wettability of the sealing agent, promote the sealing agent to spread on the coal rock surface, further promote the sealing agent to penetrate into the cracks, and improve the sealing effect; sodium aminosulfonate is also added to the composite additive, which can effectively promote the dispersion of cement particles in the cement mortar and improve the fluidity of the mortar, so that the prepared sealing agent has a high fluidity and is easy to penetrate into the cracks. Therefore, under the action of the composite additive, the fluidity of the sealing agent can be further enhanced, and the penetration effect and sealing rate of the sealing agent on the cracks can be improved. However, too high fluidity can cause the sealing agent to flow easily before it is fully solidified, forming gaps, thereby affecting the sealing effect. Therefore, inhibitory microspheres are also added to the sealer. Since cement mortar is alkaline, the glycerol tristearate contained in the mixed sol on the surface of the inhibitory microspheres will gradually hydrolyze in an alkaline environment, causing the inhibitory microspheres to gradually expose the internal inhibitory particles. The sodium persulfate in the inhibitory particles can oxidize the sodium aminosulfonate in the sealer, causing the sodium aminosulfonate to fail, and the dispersing effect of sodium aminosulfonate on the cement mortar is reduced, thereby reducing the fluidity of the sealer and reducing the subsequent flow of the sealer, preventing pores or holes caused by the loss of the sealer, and improving the sealing effect of the sealer; wherein the silica sol can cover the surface of the cement particles to form a firm silica gel film, promote the adhesion and solidification of the cement slurry, and improve the bonding strength of the cement slurry, thereby improving the compressive strength of the cement slurry. At the same time, the silica sol can also absorb moisture in the cement slurry, accelerate the coagulation of the cement slurry, shorten the coagulation time, further inhibit the gaps caused by the flow of the sealer, and improve the sealing effect. Therefore, under the combined action of the composite additive and the inhibitory microspheres, the sealing agent is promoted to penetrate into the sandstone cracks around the borehole while reducing the gaps formed by the flow of the sealing agent.
[0021] Beneficial effects:
[0022] The sealing agent prepared by the present invention can effectively penetrate into the fracture zone of coal rock and can quickly seal the hole, greatly improving the sealing effect. It effectively improves the safety and efficiency of coal mine production, reduces rework and maintenance caused by poor sealing, and thus reduces the overall cost. Therefore, the sealing agent prepared by the present invention can effectively promote the development of coal mine production. DETAILED DESCRIPTION
[0023] The present invention will be described in detail below with reference to specific embodiments:
[0024] Embodiment 1:
[0025] Preparation of composite additives:
[0026] 1 g of sodium oleate was added to 80 g of water at 70° C., and the mixture was stirred evenly to obtain a sodium oleate solution. After the solution was cooled to room temperature, 1.6 g of sodium aminosulfonate was added, and the mixture was stirred evenly to obtain a composite additive.
[0027] Preparation of inhibitory microspheres:
[0028] (1) adding 2 g of sodium persulfate to 20 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 3 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0029] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0030] (3) adding 5 g of glyceryl tristearate to 10 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0031] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0032] Preparation of sealing agent:
[0033] 4.5 kg of silicate cement, 0.5 kg of bentonite, 0.8 kg of fly ash, 0.5 kg of epoxy resin and 10 kg of water were mixed evenly, and then 0.5 kg of composite additives and 0.4 kg of inhibitory microspheres were added and mixed evenly to obtain a sealing agent.
[0034] Embodiment 2:
[0035] Preparation of composite additives:
[0036] 1.25 g of sodium oleate was added to 100 g of water at 75° C., and the mixture was stirred to obtain a sodium oleate solution. After the solution was cooled to room temperature, 1.8 g of sodium aminosulfonate was added, and the mixture was stirred to obtain a composite additive.
[0037] Preparation of inhibitory microspheres:
[0038] (1) adding 2.2 g of sodium persulfate to 22 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 3.5 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0039] (2) adding 4.5 g of sodium carboxymethyl cellulose and 0.22 g of N,N-methylenebisacrylamide to 112 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4.5:1.25, stirring evenly to obtain a mixed gel, drying the mixed gel at 35° C. for 5 h, and then crushing to obtain inhibitory particles with a particle size of 3 mm;
[0040] (3) adding 5.5 g of glyceryl tristearate to 11 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 5.5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0041] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0042] Preparation of sealing agent:
[0043] 4.8 kg of silicate cement, 0.65 kg of bentonite, 0.65 kg of fly ash, 0.65 kg of epoxy resin and 12.5 kg of water were added and stirred evenly, and then 0.65 kg of composite additives and 0.5 kg of inhibitory microspheres were added and stirred evenly to obtain a sealing agent.
[0044] Embodiment 3:
[0045] Preparation of composite additives:
[0046] 1.5 g of sodium oleate was added to 120 g of water at 80° C., and the mixture was stirred evenly to obtain a sodium oleate solution. After the solution was cooled to room temperature, 2 g of sodium aminosulfonate was added, and the mixture was stirred evenly to obtain a composite additive.
[0047] Preparation of inhibitory microspheres:
[0048] (1) adding 2.4 g of sodium persulfate to 24 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 4 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0049] (2) adding 5 g of sodium carboxymethyl cellulose and 0.25 g of N,N-methylenebisacrylamide to 125 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 5:1.5, stirring evenly to obtain a mixed gel, drying the mixed gel at 40° C. for 6 h, and then crushing to obtain inhibitory particles with a particle size of 5 mm;
[0050] (3) adding 6 g of glyceryl tristearate to 12 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 6 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0051] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0052] Preparation of sealing agent:
[0053] 5 kg of silicate cement, 0.5 kg of bentonite, 0.8 kg of fly ash, 0.5 kg of epoxy resin and 10 kg of water were mixed evenly, and then 0.8 kg of composite additives and 0.6 kg of inhibitory microspheres were added and mixed evenly to obtain a sealing agent.
[0054] Comparative Example 1:
[0055] This comparative example is in contrast to Example 1, the only difference being the difference in the composite additive, specifically, no sodium oleate is added, and the specific method is as follows:
[0056] 1.6 g of sodium sulfamate was added into 80 g of water and stirred to obtain a composite additive.
[0057] The preparation method of the inhibitor microspheres and the sealing agent used in this comparative example is the same as that in Example 1.
[0058] Comparative Example 2:
[0059] This comparative example is in contrast to Example 1, the only difference being the difference in the composite additive, specifically, no sodium aminosulfonate is added, and the specific method is as follows:
[0060] 1 g of sodium oleate was added into 80 g of water at 70° C., stirred evenly and then cooled to room temperature to obtain a composite additive.
[0061] The preparation method of the inhibitor microspheres and the sealing agent used in this comparative example is the same as that in Example 1.
[0062] Comparative Example 3:
[0063] This comparative example is in contrast to Example 1, the only difference being the difference in the inhibition of microspheres, specifically, no sodium persulfate is added, and the specific method is as follows:
[0064] (1) Add 3 g of silica sol to 20 g of water and mix well to obtain a mixed solution;
[0065] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0066] (3) adding 5 g of glyceryl tristearate to 10 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0067] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0068] The preparation method of the composite additive and sealing agent used in this comparative example is the same as that in Example 1.
[0069] Comparative Example 4:
[0070] This comparative example is compared with Example 1, and the difference is only in the difference in the inhibition of microspheres, specifically, no silica sol is added, and the specific method is as follows:
[0071] (1) adding 2 g of sodium persulfate to 20 g of water and mixing evenly to obtain a sodium persulfate solution;
[0072] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with a sodium persulfate solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0073] (3) adding 5 g of glyceryl tristearate to 10 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0074] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0075] The preparation method of the composite additive and sealing agent used in this comparative example is the same as that in Example 1.
[0076] Comparative Example 5:
[0077] This comparative example is in contrast to Example 1, the only difference being that the microspheres are inhibited differently, specifically, no glyceryl tristearate solution is added, and the specific method is as follows:
[0078] (1) adding 2 g of sodium persulfate to 20 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 3 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0079] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0080] (3) Mix 5 g of gelatin with 100 g of water and heat until the gelatin is completely dissolved to obtain a gelatin sol;
[0081] (4) Adding the inhibitory particles into the gelatin solution so that the inhibitory particles are completely wrapped by the gelatin solution to obtain inhibitory microspheres.
[0082] The preparation method of the composite additive and sealing agent used in this comparative example is the same as that in Example 1.
[0083] Comparative Example 6:
[0084] This comparative example is in contrast to Example 1, the only difference being the difference in the inhibition of microspheres, specifically, the mass ratio of glyceryl tristearate to gelatin is 1:2, and the specific method is as follows:
[0085] (1) adding 2 g of sodium persulfate to 20 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 3 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0086] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0087] (3) adding 2.5 g of glyceryl tristearate to 10 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0088] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0089] The preparation method of the composite additive and sealing agent used in this comparative example is the same as that in Example 1.
[0090] Comparative Example 7:
[0091] This comparative example is in contrast to Example 1, the only difference being the difference in the inhibition of microspheres, specifically, the mass ratio of glyceryl tristearate to gelatin is 2:1, and the specific method is as follows:
[0092] (1) adding 2 g of sodium persulfate to 20 g of water and mixing them uniformly to obtain a sodium persulfate solution, then adding 3 g of silica sol to the sodium persulfate solution and stirring them uniformly to obtain a mixed solution;
[0093] (2) adding 4 g of sodium carboxymethyl cellulose and 0.2 g of N,N-methylenebisacrylamide to 100 g of water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then mixing the sodium carboxymethyl cellulose gel with the mixed solution at a mass ratio of 4:1, stirring evenly to obtain a mixed gel, drying the mixed gel at 30° C. for 4 h, and then crushing to obtain inhibitory particles with a particle size of 2 mm;
[0094] (3) adding 5 g of glyceryl tristearate to 10 g of anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding 2.5 g of gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol;
[0095] (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
[0096] The preparation method of the composite additive and sealing agent used in this comparative example is the same as that in Example 1.
[0097] experiment:
[0098] 1. Preparation of sealing agent:
[0099] 4.5 kg of silicate cement of model P·O42.5, 0.5 kg of bentonite, 0.8 kg of fly ash, 0.5 kg of epoxy resin and 10 kg of water were mixed evenly, and then 0.5 kg of composite additives and 0.4 kg of inhibitory microspheres were added and mixed evenly to obtain a sealing agent.
[0100] 2. According to the above preparation method, the composite additives and inhibitory microspheres used in the preparation of the sealing agent in each experimental group are selected as follows:
[0101] (1) Experimental group 1 used the composite additive and inhibitory microspheres prepared in Example 1;
[0102] (2) Comparative Group 1-2 used the composite additive prepared in Comparative Examples 1-2 and the inhibitory microspheres prepared in Example 1;
[0103] (3) Comparative groups 3-7 used the inhibitory microspheres prepared in Comparative Examples 3-7 and the composite additive prepared in Example 1;
[0104] (4) No composite additive was added to control group 8, no inhibitory microspheres were added to control group 9, and no composite additive or inhibitory microspheres were added to the blank group.
[0105] 3. Detection method:
[0106] (1) Determination of fluidity: The test was conducted using the cone section mold method. The prepared sealant was poured into the cone section mold, and then the cone section mold was slowly lifted vertically upward. The diffusion radius of the slurry was measured using a steel ruler. This was repeated three times, and the average value of the results was taken.
[0107] (2) Determination of setting time: The setting time method in GB1346-89 "Test Methods for Water Consistency, Setting Time and Stability of Cement Standard Consistency" was used to determine the setting time. The prepared sealant was injected into a round mold, and the setting time was determined after it was scraped flat. This was repeated three times, and the average value of the results was taken.
[0108] (3) Determination of compressive strength: The cement paste was uniformly and quickly injected into a 70 mm × 70 mm × 70 mm triple mold coated with a release agent. The mold was slightly shaken to reduce the number of bubbles in the paste, and the upper surface was scraped flat. After final setting, the mold was removed. Under natural curing conditions, the compressive strength after 24 h was measured according to the "Test Method for Cement Mortar Strength". This was repeated three times and the results were averaged.
[0109] The results of the measured fluidity, setting time and compressive strength are shown in Table 1.
[0110] Table 1
[0111] Initial setting time (min) Final setting time (min) Fluidity(mm) Compressive strength(Mpa) Experimental Group 1 441 492 235 6.4 Comparison group 1 422 476 187 6.5 Comparison group 2 415 469 182 6.5 Comparison group 3 564 618 232 5.6 Comparison group 4 550 605 233 5.6 Comparison group 5 534 588 234 5.5 Comparison group 6 545 597 233 6.3 Comparison group 7 462 503 204 6.3 Comparison group 8 401 452 166 6.5 Comparison group 9 602 658 233 5.2 Blank Group 454 508 167 5.9
[0112] Analyzing Table 1, we can get:
[0113] 1. Compared with experimental group 1, the difference between comparative group 1-2 is only the raw materials of the composite additive. Compared with experimental group 1, comparative group 1 does not add sodium oleate, and the fluidity of the sealing agent is poor and the penetration effect is poor. This is because sodium oleate can increase the wettability of the sealing agent, promote the spreading of the sealing agent on the surface of coal rock, and then promote the penetration of the sealing agent into the cracks. Comparative group 1 does not add sodium oleate, resulting in poor sealing effect of comparative group 1. Compared with experimental group 1, comparative group 2 does not add sodium aminosulfonate, and the fluidity of the sealing agent is poor, and it cannot penetrate well into the cracks, which leads to poor sealing effect of the sealing agent. At the same time, since sodium aminosulfonate has a slow setting effect on cement slurry, it will cause the setting time of cement slurry to become longer. Therefore, the setting time of the sealing agent in experimental group 1 is longer than that in comparative group 2. In comparison group 8, no composite additives were added, and the fluidity of the sealant was low, resulting in the sealant not being able to penetrate into the cracks well, resulting in a poor sealing effect. At the same time, since no composite additives were added, the setting time of the sealant was short.
[0114] 2. Compared with experimental group 1, the difference between comparative groups 3-5 lies only in the difference in the raw materials for inhibiting microspheres. Compared with experimental group 1, comparative group 3 does not add sodium persulfate, and the fluidity of the sealant is good. This is because sodium persulfate can oxidize sodium aminosulfonate, causing it to lose its retarding effect on cement slurry and reduce the fluidity of the sealant. Therefore, the sealing effect of comparative group 3 is poor and the strength is low. Compared with experimental group 1, comparative group 4 does not add silica sol, and the fluidity of the sealant is good and the setting time is long. This is because silica sol can cover the surface of cement particles to form a firm silica film, promote the bonding and curing of cement slurry, and improve the bonding strength of the sealant. It can also absorb moisture in cement slurry and accelerate the coagulation of cement slurry. Comparative group 4 does not add silica sol, so its setting time is long, and the sealant with high fluidity is easy to flow before it is completely cured, resulting in poor sealing effect and the formation of gaps. Compared with experimental group 1, control group 5 did not add glyceryl tristearate, and the inhibitory microspheres needed a longer time to expose the active ingredients. During this period, the sealant was prone to flow and cause gaps, and the sealing effect was poor. Compared with experimental group 1, control group 9 did not add inhibitory microspheres, and the sealant had good fluidity, but the sealant could not bond well with the cracks after penetrating into the cracks, resulting in an increase in the coagulation time of the sealant.
[0115] 3. Compared with experimental group 1, the mass ratio of glyceryl tristearate to gelatin in comparison group 6 was 1:2, and the content of glyceryl tristearate was low. It took a long time for the inhibition microspheres to expose the internal inhibition particles, which caused the sealing agent to flow before solidification and form gaps, resulting in poor sealing effect. Compared with experimental group 1, the mass ratio of glyceryl tristearate to gelatin in comparison group 7 was 2:1, and the content of glyceryl tristearate was high. The inhibition particles were exposed quickly, resulting in low fluidity of the sealing agent.
[0116] 4. The blank group was compared with experimental group 1. The difference was that the blank group did not add composite additives and inhibitory microspheres when preparing the sealing agent. The prepared sealing agent had poor fluidity and was not easy to flow into the cracks, resulting in low permeability of the sealing agent and poor sealing effect. At the same time, the absence of inhibitory microspheres caused the sealing agent to coagulate slowly. However, since the blank group did not add composite additives, its coagulation time increased. Compared with control group 6, the blank group did not add inhibitory microspheres, resulting in a longer coagulation time.
[0117] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A sealing agent for coal mines, characterized in that: The raw materials of the sealing agent are as follows: cement, bentonite, fly ash, epoxy resin, composite additives, inhibitory microspheres, and water, and the mass ratio thereof is (45-50): (5-8): (2-3): (8-10): (5-8): (4-6): (100-150).
2. The sealing agent for coal mines according to claim 1, characterized in that: The raw materials of the composite additive are as follows: sodium oleate, sodium aminosulfonate and water, and the mass ratio thereof is (1-1.5): (1.6-2): (80-120).
3. The sealing agent for coal mines according to claim 2, characterized in that: The preparation method of the composite additive is as follows: Sodium oleate is added into water at 70-80° C., and stirred evenly to obtain a sodium oleate solution. After the solution is cooled to room temperature, sodium aminosulfonate is added thereto, and stirred evenly to obtain a composite additive.
4. The sealing agent for coal mines according to claim 3, characterized in that: The preparation method of the inhibitory microspheres is as follows: (1) adding sodium persulfate to water and mixing uniformly to obtain a sodium persulfate solution, then adding silica sol to the sodium persulfate solution and stirring uniformly to obtain a mixed solution; (2) adding sodium carboxymethyl cellulose and N,N-methylenebisacrylamide to water, stirring evenly to obtain sodium carboxymethyl cellulose gel, then adding the mixed solution, stirring evenly to obtain a mixed gel, drying the mixed gel at 30-40° C. for 4-6 hours, and then crushing to obtain inhibitory particles; (3) adding glyceryl tristearate to anhydrous ethanol, heating the ethanol until it is completely dissolved, adding water and mixing evenly to obtain a 5 wt % tristearate solution, then adding gelatin, and continuing to heat until the gelatin is completely dissolved to obtain a mixed sol; (4) Adding the inhibition particles into the mixed sol so that the inhibition particles are completely wrapped by the mixed sol to obtain inhibition microspheres.
5. The sealing agent for coal mines according to claim 4, characterized in that: In the step (1) of preparing the inhibitory microspheres, the mass ratio of sodium persulfate, silica sol and water is (2-2.4): (3-4): (20-24).
6. The sealing agent for coal mines according to claim 5, characterized in that: The mass ratio of sodium carboxymethyl cellulose, N,N-methylenebisacrylamide and water in the preparation step (2) of the inhibitory microspheres is (4-5):(0.2-0.25):(100-125), and the mass ratio of sodium carboxymethyl cellulose gel and the mixed solution is (4-5):(1-1.5).
7. The sealing agent for coal mines according to claim 6, characterized in that: In the step (3) of preparing the inhibitory microspheres, the mass ratio of tristearate to gelatin is 1:
1.
8. The sealing agent for coal mines according to claim 7, characterized in that: The particle size of the inhibitory microspheres is 2-5 mm.
9. The sealing agent for coal mines according to claim 1, characterized in that: The particle size of the fly ash is 0.3-0.6 mm, and the particle size of the bentonite is 0.1-0.5 mm.